2007
DOI: 10.2337/db06-1660
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Prandial Blood Glucose and Improvement of Glucose Tolerance by Liver-Specific Inhibition of SH2 Domain–Containing Inositol Phosphatase 2 (SHIP2) in Diabetic KKAy Mice

Abstract: Type 2 diabetes is characterized by a progressive resistance of peripheral tissues to insulin. Recent data have established the lipid phosphatase SH2 domain-containing inositol phosphatase 2 (SHIP2) as a critical negative regulator of insulin signal transduction. Mutations in the SHIP2 gene are associated with type 2 diabetes. Here, we used hyperglycemic and hyperinsulinemic KKA y mice to gain insight into the signaling events and metabolic changes triggered by SHIP2 inhibition in vivo. Liver-specific expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
9
27
0
Order By: Relevance
“…Regarding the PTEN, it was reported that the deletion of PTEN in liver resulted in steatohepatitis along with enhanced liver insulin action with improved systemic glucose tolerance (17,18). Later studies supported this notion, as the loss of PTEN activity increased lipid substrate availability in the face of reduced hepatic lipoprotein production capacity leading to hepatosteatosis and fatty liver (19). These studies have shown a role for PTEN in regulating lipogenesis in liver cells; however, less information is available on the role of another lipid phosphatase, SHIP2, in liver lipid and lipoprotein metabolism.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Regarding the PTEN, it was reported that the deletion of PTEN in liver resulted in steatohepatitis along with enhanced liver insulin action with improved systemic glucose tolerance (17,18). Later studies supported this notion, as the loss of PTEN activity increased lipid substrate availability in the face of reduced hepatic lipoprotein production capacity leading to hepatosteatosis and fatty liver (19). These studies have shown a role for PTEN in regulating lipogenesis in liver cells; however, less information is available on the role of another lipid phosphatase, SHIP2, in liver lipid and lipoprotein metabolism.…”
Section: Introductionmentioning
confidence: 91%
“…SHIP2 overexpression leads to inhibition of insulininduced Akt activation, glucose uptake, and glycogen synthesis in 3T3-L1 adipocytes, L6 myotubes [18] and tissues of animal models [19,20]. In addition, liver-specific down regulation or inhibition of SHIP2 improves the insulin signaling in mice [19,21]. Furthermore, the heterozygous knockout mice of SHIP2 gene were resistant against high-fat diet-induced obesity and insulin resistance [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…SHIP2 modulation on insulin sensitivity in models of type 2 diabetes. Adenoviral expression of a dominant-negative mutant SHIP2 in the liver of obese hyperglycemic mice restored insulin sensitivity and Akt phosphorylation (22), whereas the expression of wild-type SHIP2 blunted these (23). In humans, SHIP2 (Inppl1) polymorphisms are associated with obesity, type 2 diabetes, and the metabolic syndrome (24,25).…”
Section: Ship2 Insulin Signaling Pi3k and Aktmentioning
confidence: 99%
“…Lipid phosphatase SHIP2 downregulates PI3K mediated signalling, induced by insulin and other growth factors, by hydrolyzing PI(3,4,5,)P 3 to PI(3,4)P 2 (Blero et al 2001. SHIP2 overexpression in mice has a negative effect on glucose tolerance (Kagawa et al 2008,Fukui et al 2005 and SHIP2 knockout mice appear resistant to high fat diet-induced obesity and insulin resistance (Sleeman et al 2005), and in addition, inhibition of SHIP2 in the liver has been shown to improve glucose tolerance in diabetic mice (Grempler et al 2007). Taken together, SHIP2 is a downregulator of PI3K mediated insulin signalling, that is known to function in liver, muscle and adipose cells, but its role in the kidney has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%